ROLE OF SERUM FERRITIN IN CRITICALLY ILL PATIENTS - SUMATHI.K.; SHANTHI.B (International Journal of Pharma and Bio Sciences, 2014)
Ferritin being an acute phase reactant serves as a useful inflammatory marker in chronic inflammatory disorders. The aim of the study is to study the meaningful association between chronic inflammation and ferritin. 50 critically ill patients admitted in the intensive care unit of Sree Balaji Medical College & Hospital and 50 healthy controls were included in this study. Particle enhanced turbidimetric immunoassay was the method used to estimate serum ferritin for both cases & controls. 72% of cases had increased ferritin which is significant, whereas only 2% had slight increase in serum ferritin level in control. From this study it is concluded that it is mandatory to estimate the serum ferritin in critically ill patients as the increase of ferritin concentration correlates the worsening clinical status in severely ill patients.